Utilizing of Adsorptive Transfer Stripping Technique Brdicka Reaction for Determination of Metallothioneins Level in Melanoma Cells, Blood Serum and Tissues - Krizkova, Sona; Fabrik, Ivo; Adam, Vojtech; Kukacka, Jiri; Prusa, Richard; Chavis, Grace J; Trnkova, Libuse; Strnadel, Jan; Horak, Vratislav; Kizek, Rene (Sensors (Basel, Switzerland), 2008)
In the paper we utilized the adsorptive transfer stripping differential pulse voltammetry Brdicka reaction for the determination of metallothioneins (MT) in melanoma cells, animal melanoma tissues (MeLiM miniature pig) and blood serum of patients with malignant melanoma. Primarily we attempted to investigate the influence of dilution of real sample on MT electrochemical response. Dilution of samples of 1 000 times was chosen the most suitable for determination of MT level in biological samples. Then we quantified the MT level in the melanoma cells, the animal melanoma tissues and the blood serum samples. The MT content in the cells varied within the range from 4.2 to 11.2 μM. At animal melanoma tissues (melanomas localized on abdomen, back limb and dorsum) the highest content of MT was determined in the tumour sampled on the back of the animal and was nearly 500 μg of MTs per gram of a tissue. We also quantified content of MT in metastases, which was found in liver, spleen and lymph nodes. Moreover the average MT level in the blood serum samples from patients with melanoma was 3.0 ± 0.8 μM. MT levels determined at melanoma samples were significantly (p < 0.05) higher compared to control ones at cells, tissues and blood serum.
Keywords: Adsorptive Transfer Stripping Technique; Brdicka Reaction; Metallothionein; Cell; Animal Tissue; Human blood serum; Tumour Marker; Differential Pulse Voltammetry; Protein